Deetiolation Enhances Phototropism by Modulating NON-PHOTOTROPIC HYPOCOTYL3 Phosphorylation Status. Issue 2 (27th March 2019) - Sullivan, Stuart; Kharshiing, Eros; Laird, Janet; Sakai, Tatsuya; Christie, John M.
Abstract : Phototropism is enhanced by seedling de-etiolation and is achieved by a molecular rheostat that fine-tunes the phosphorylation and localization status of the phototropic signaling component, NPH3. Abstract: Phototropin (phot) receptor kinases play important roles in promoting plant growth by controlling light-capturing processes, such as phototropism. Phototropism is mediated through the action of NON-PHOTOTROPIC HYPOCOTYL3 (NPH3), which is dephosphorylated following phot activation. However, the functional significance of this early signaling event remains unclear. Here, we show that the onset of phototropism in dark-grown (etiolated) seedlings of Arabidopsis ( Arabidopsis thaliana ) and tomato ( Solanum lycopersicum ) is enhanced by greening (deetiolation). Red and blue light were equally effective in promoting phototropism in Arabidopsis, consistent with our observations that deetiolation by phytochrome or cryptochrome was sufficient to enhance phototropism. Increased responsiveness did not result from an enhanced sensitivity to the phytohormone auxin, nor does it involve the phot-interacting protein, ROOT PHOTOTROPISM2. Instead, deetiolated seedlings showed attenuated levels of NPH3 dephosphorylation and diminished relocalization of NPH3 from the plasma membrane during phototropism. Likewise, etiolated seedlings that lack the PHYTOCHROME-INTERACTING FACTORS (PIFs) PIF1, PIF3, PIF4, and PIF5 displayed reduced NPH3 dephosphorylation and enhanced phototropism, consistent with their constitutive photomorphogenic phenotype in darkness. Phototropic enhancement could also be achieved in etiolated seedlings by lowering the light intensity to diminish NPH3 dephosphorylation. Thus, phototropism is enhanced following deetiolation through the modulation of a phosphorylation rheostat, which in turn sustains the activity of NPH3. We propose that this dynamic mode of regulation enables young seedlings to maximize their establishment under changing light conditions, depending on their photoautotrophic capacity.